Usability of a telerehabilitation program for patients with musculoskeletal or oncological diseases: A mixed-methods evaluation / Benutzerfreundlichkeit eines Telerehabilitations-Programmes für Patient*innen mit muskuloskelettalen oder onkologischen Erkrankungen: Eine Mixed-Methods Evaluation - Stöhr Doreen; Matzka Martin; Gschwenter Stefan; Edlmayer Alexandra; Felder David; Spary Andreas; Reiger Gabriele; Honegger Martina; Skoumal Martin (International Journal of Health Professions)
Telerehabilitation may stabilize the results of a previous phase 2 rehabilitation program through remote rehabilitation sessions. We evaluated a new telerehabilitation service (PV RehaTRAIN®) during its initial implementation, focusing on its usability both from the perspective of patients with musculoskeletal or oncological diseases and the interdisciplinary treatment team.